Dual tri-isolated DC H-6 inverter with minimal power components design - Maheswaran, Anusuya; Ramanujam, Geetha; Rengaraju, Ilango; Arumugam, Iyyappan S.; Ramachandran, Gayathri (Institute of Advanced Engineering and Science, 2024)
Multilevel inverters have been forecasted in recent years for industrial and renewable energy applications due to its inherent characteristics of shaping the output voltage nearer to sinusoidal shape through concatenating several two/three level inverters using isolated DC sources or DC-link capacitors. However, the classical topologies used for synthesizing stepped voltage have several outwards like more number of DC sources or DC-link capacitors and switching devices used. In this paper, an effort has been sighted to bring a new topology for generating stepped voltage to overcome the above mentioned demerits. In addition to this, a new digital pulse width modulation (PWM) strategy is developed in-line with a new topology to eliminate the use of carrier and reference signals. The performance of the proposed topology and developed control strategy are evaluated in MATLAB/ Simulink platform and an laboratory prototype is constructed for experimental investigations to accord the simulation results.